Análise energética da aplicação de torta de filtro na substituição parcial da adubação inorgânica sintética da cana-de-açúcar - Innocente, Andréia Franco [UNESP] (2015)
Synthetic inorganic fertilizers highly depend on external energy from nonrenewable resources. The indiscriminate use of these finite energy resources threatens the sustainability of production systems and contributes to environmental degradation. As a means to minimize fossil fuels consumption and improve energy efficiency of agricultural systems, filter cake, a by-product of sugarcane processing, can be used for the partial substitution of synthetic inorganic fertilizers in sugarcane cultivation. The current work aims at analyzing the energy flows involved in the use of filter cake for sugarcane fertilization at Usina São Manoel and at comparing it with the same flows when only synthetic inorganic fertilizers are used without filter cake. We used primary and secondary data for this study. The energy inputs were classified and quantified according to their types (direct energy or indirect energy), considering that direct energy is divided in biological or fossil and indirect energy as industrial energy. The direct energy from biological origin was composed of manpower, biodiesel and filter cake; as direct energy from fossil origin, we quantified diesel oil, lubricant and synthetic inorganic fertilizers with nitrogen; the indirect energy from industrial origin was obtained for machines, implements, equipment and synthetic inorganic fertilizers (NPK). Part of the energy cost with the synthetic inorganic fertilizers with nitrogen (34.2%) was relocated to a fossil resources for the classification of the energy inputs to become closer to reality. It was obtained as a result that fertilization systems without filter cake depend less on fuels from external fossil resources. For the filter cake fertilization system, some alternatives could be adopted by the factory under study for reducing the use of fossil fuels, specifically diesel oil, which is the biggest contributor to nonrenewable energy inputs in this ...